Studying the impact of climate change on spatiotemporal variability of blue and green water resources - Saadatpour, M.; Kamali, F. (IWA Publishing, 2025)
Nowadays, the focal point of water resources planning and management in the river basin scale, especially in the arid/semi-arid regions, is aimed at enhancing the efficient utilization of water resources. Therefore, knowledge on the spatiotemporal variations of water resources concerning blue water (BW) and green water (GW) indicators under climate change scenarios is inevitable. The present research was conducted to study the interaction of climate variability on the BW and GW components in the Seymareh River Basin (SRB), Iran, with the aid of the Soil and Water Assessment Tool (SWAT). Future climate scenarios for the period of 2020–2040 were generated based on the LARS-WG 6.0 model. According to the results, all climate change scenarios indicate an increase in precipitation in the range of 29–33%. Furthermore, the average monthly surface runoff was projected to increase approximately by 75, 88, and 98% under RCP 4.5, 6.0, and 8.5 scenarios, respectively. The results revealed that the SRB witnessed a significant increase in BW due to climate changes. Meanwhile, the magnitude of the GW indicator was different within the SRB, with minor changes. Identifying areas with high blue/green water potentials is effective in planning for rain-fed or irrigated agriculture in the SRB.